METHODOLOGY FOR THE ALTERATION OF HAZARDOUS SOLVENTS IN DRUG SYNTHESIS - Helal Uddin, A.B.M. (2021)
Hazardous solvents have a high potential for causing acute health risks, including serious health problems such as cancer. They should be avoided or limited in pharmaceutical and chemical synthesis owing to the health hazards and safety issues. A method of amide coupling reaction was developed employing the recommended solvents to replace the hazardous solvents. The reactions were observed using the RP-HPLC method to detect reaction rate of aniline and benzoic acid to produce N-phenyl benzamide. 68.33%, 79.25% and 89.81% yields were synthesized using the solvents: acetone (Ace), dimethyl sulfoxide (DMSO), and ethanol (EtOH) respectively while 87.60% was produced by hazardous solvent: N, N-dimethyl formamide (DMF). Using this approach, adjusting the pH10 of the organic solvent increases reaction yield up to 34.67%, 4.65%, and 3.84% for Ace, DMSO, and EtOH, respectively. In drug synthesis, the proposed method can be applied in wide range to get the protection from the risks of hazardous solvents. The method can be anticipated in future to be an exciting basic method in synthetic chemistry.